2020
DOI: 10.1038/s41598-020-74387-0
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging and pathological comparison of early hypoxic–ischemic brain damage in newborn piglets

Abstract: To investigate the application value of magnetic resonance diffusion kurtosis imaging (DKI) in hypoxic–ischemic brain damage (HIBD) in newborn piglets and to compare imaging and pathological results. Of 36 piglets investigated, 18 were in the experimental group and 18 in the control group. The HIBD model was established in newborn piglets by ligating the bilateral common carotid arteries and placing them into hypoxic chamber. All piglets underwent conventional MRI and DKI scans at 3, 6, 9, 12, 16, and 24 h pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The pattern of HI injury observed by MK, with a sharp increase in the MK value of the lesion region at 12 h post-injury, demonstrates a dramatic change in the degree of injury between 0 and 12 h, indicating rapid progression of hypoxic and ischemic brain cytotoxic edema. This finding is in agreement with the results of Xiao et al ( 2020 ) and Ma et al ( 2022 ), suggesting a continuous deterioration of the lesion. Then, it gradually decreased over 5 days, approaching baseline levels, but it still remained higher than that in the controls.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The pattern of HI injury observed by MK, with a sharp increase in the MK value of the lesion region at 12 h post-injury, demonstrates a dramatic change in the degree of injury between 0 and 12 h, indicating rapid progression of hypoxic and ischemic brain cytotoxic edema. This finding is in agreement with the results of Xiao et al ( 2020 ) and Ma et al ( 2022 ), suggesting a continuous deterioration of the lesion. Then, it gradually decreased over 5 days, approaching baseline levels, but it still remained higher than that in the controls.…”
Section: Discussionsupporting
confidence: 94%
“…Some studies suggest that testosterone may worsen injury (Hill et al, 2011 ) or that estrogen may have a protective effect (Nematipour et al, 2020 ), while others indicate that sex differences in cell death pathways may favor females (Renolleau et al, 2007 ; Charriaut-Marlangue et al, 2018 ; Bonnin et al, 2020 ). Recently, advanced neuroimaging methods such as magnetic resonance imaging (MRI), diffusion-weighted MRI, and magnetic resonance spectroscopy have been used to quantify brain damage and metabolite abnormalities in HI models at different time points after injury (Zhu et al, 2008 ; van de Looij et al, 2011 ; Huang et al, 2016 ; Xiao et al, 2020 ; Tabacaru et al, 2023 ). A previous study showed that PND7 HI males developed more severe nervous brain damage, reflex deficits, hemiplegia, and memory impairment than females (Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher FA values indicate more intact axon fibers. MD reflects the overall level of molecular diffusion and diffusion resistance 18. The MD coefficient varies according to the progressive stage of the injury, leading to an overall measurement of water molecule movements.…”
Section: Discussionmentioning
confidence: 99%
“…MD reflects the overall level of molecular diffusion and diffusion resistance. 18 The MD coefficient varies according to the progressive stage of the injury, leading to an overall measurement of water molecule movements. The primary diffusion metrics (FA and MD) reflect overall white matter health, organization, and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a much larger difference of mean diffusivities is observed in brain tissue (~10 fold lower in the post-mortem than in vivo). These differences might be explained by death related changes such as postmortem cell swelling (Toorn et al, 1996;Xiao et al, 2020).…”
Section: Structural and Diffusion Data Quality Assessmentmentioning
confidence: 99%